2018
DOI: 10.1016/j.athoracsur.2017.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Leaflet Stress in Surgery for Genetically Determined Root Aneurysms: Biomechanical Insights

Abstract: We are grateful to Tasca and colleagues [1] for their comparative biomechanical study of valve-sparing root replacement with the sleeve or David techniques. We believe that their results and our own studies of flow and wall stress after personalized external aortic root support (PEARS) are complementary [2,3]. Our studies with sheep [4,5] show consistently that the PEARS mesh is incorporated into the aortic wall, which is stabilized and believed to be structurally as strong as a tube graft. We are particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Our numerical simulations showed that after the sleeve procedure, stresses in the leaflet belly, at the commissures, and at the interleaflets triangles, respectively, are 35%, 44%, and 28% lower than those associated with the David procedure [2]. Motivated by Izgi and colleagues [1], we further analyzed our data focusing on the diastolic geometry of the aortic root, as increased peak stresses may be associated with geometrical factors: leaflet curvature, because stresses in pressurized membranous structures depend on curvature; and discontinuities at the leaflet-graft transition, which may induce stress concentrations or influence leaflet configuration. Our results suggest that geometrical discontinuities at the leaflet-graft transition likely play a role.…”
Section: Replymentioning
confidence: 77%
See 4 more Smart Citations
“…Our numerical simulations showed that after the sleeve procedure, stresses in the leaflet belly, at the commissures, and at the interleaflets triangles, respectively, are 35%, 44%, and 28% lower than those associated with the David procedure [2]. Motivated by Izgi and colleagues [1], we further analyzed our data focusing on the diastolic geometry of the aortic root, as increased peak stresses may be associated with geometrical factors: leaflet curvature, because stresses in pressurized membranous structures depend on curvature; and discontinuities at the leaflet-graft transition, which may induce stress concentrations or influence leaflet configuration. Our results suggest that geometrical discontinuities at the leaflet-graft transition likely play a role.…”
Section: Replymentioning
confidence: 77%
“…Subsequent clinical follow-up studies have shown that the leaflets generally prove durable. This new study of the biomechanics of valve-sparing root replacement adds further reassuring information that may be directly applicable to PEARS [1]. Specifically, their study indicates that preserved leaflet and sinus continuity may be a favorable feature of the sleeve compared with the David.…”
mentioning
confidence: 74%
See 3 more Smart Citations